Addition of the microchromosome GGA25 to the chicken genome sequence assembly through radiation hybrid and genetic mapping - Douaud, M.; Feve, K.; Gerus, M.; Fillon, V.; Bardes, S.; Gourichon, D.; Dawson, D.A.; Hanotte, Olivier H.; Burke, T.; Vignoles, F.; Morrison, M.; Tixier-Boichard, M.; et al. (Springer, 2008)
The publication of the first draft chicken sequence assembly became available in 2004 and was updated in 2006. However, this does not constitute a definitive and complete sequence of the chicken genome, since the microchromosomes are notably under-represented. In an effort to develop maps for the microchromosomes absent from the chicken genome assembly, we developed radiation hybrid (RH) and genetic maps with markers isolated from sequence currently assigned to "chromosome Unknown" (chrUn). The chrUn is composed of sequence contigs not assigned to named chromosomes. To identify and map sequence belonging to the microchromosomes we used a comparative mapping strategy, and we focused on the small linkage group E26C13.